Pengaruh Perputaran Modal Kerja Terhadap Likuiditas Perusahaan Jasa Sub Sektor Property, Real Estate Dan Kontruksi Bangunan - Idham Saputra; Andir Indrawan; Ade Sudarma (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine the effect of working capital turnover on liquidity (Current Ratio) in the Property, Real Estate and Construction Sub Sector Services company. This research uses associative hypothesis research type. The research method used is quantitative. The sample in this study were 6 Property, Real Estate and Construction Sub Sector Services companies listed on the Indonesia Stock Exchange in the 2013-2018 period. Sampling with the type of nonprobability sampling with purposive sampling technique. The data analysis technique used is the normality test and the partial hypothesis test (t test). The results of the research, the partial hypothesis test results (t test) can be seen the t-count of the variable working capital turnover (X) of -3,735 with a significant level of 0.001, meaning that the working capital turnover has a negative effect on liquidity and the significant value shows a significant effect. In conclusion, working capital turnover has a negative effect on liquidity because of uncertain income. The higher the liquidity value, the higher the value of current assets which will also be directly proportional to the sales results. Working capital turnover is not always directly proportional to liquidity. Keywords: Working Capital Turnover, Accounts Receivable Turnover, Liquidity.